Le soi de l’apprenant d’une langue étrangère : adaptation de certaines théories psychologiques en didactique de langues - Pudo, Dorota (Neofilolog, 2021)
As an interdisciplinary science, SLA studies are receptive to ideas formulated in other disciplines. Although the relevance of psychology for SLA is often underestimated, its influence has recently grown with the advent of neurosciences and the increased interest in learner variables. One f concept from psychology that is potentially interesting is theories of the self, some of which have recently been adapted into research on foreign language learner motivation. In this article, we examine two particular psychological concepts (possible selves and self-discrepancy) as sources of an influential L2 motivation model – Dörnyei’s L2 Motivational Self System – which is very little debated in French SLA literature. We outline the main points of the three theories, analyse them and try to assess the adaptation process. As in any case of transfer between disciplines, the source theories are altered, but the result has proven a meaningful and enriching addition to studies of L2 motivation.